Asparagopsis taxiformis mitigates ruminant methane emissions via microbial modulation and inhibition of methyl-coenzyme M reductase - Li, Shuai; Sun, Yi; Cao, Siguang; Guo, Tongjun; Tong, Xiong; Zhang, Zhifei; Sun, Jiajie; Yang, Yufeng; Wang, Qing; Li, Dagang; Min, Li (Frontiers in Microbiology, 2025)
IntroductionAsparagopsis taxiformis (A. taxiformis) has shown great potential to mitigate methane (CH4) emissions in recent years. This study aims to evaluate the impact of A. taxiformis on methane emissions and to fill the knowledge gap regarding its mechanisms of action in affecting CH4 metabolism and rumen fermentation.MethodsThe experimental design consisted of a control group (CON) and test groups supplemented with 2% (Low), 5% (Mid), and 10% (High) of dried and freeze-dried treatment A. taxiformis, respectively, for 48 h of in vitro rumen fermentation. The optimal combination strategy for mitigating CH4 emissions was confirmed by analyzing nutrient degradation, CH4 production and rumen fermentation parameters, and the mechanism of action was analyzed by metagenomic and metabolomic approaches.Results and discussionThe results showed that freeze-dried treatment had better potential to mitigate CH4 emissions than dried treatment, and supplementation of freeze-dried treatments at Low, Mid, and High groups significantly reduced CH4 production by 32.44%, 98.53%, and 99.33%, respectively. However, the High group exhibited a huge negative impact on rumen fermentation. Therefore, subsequent analyses focused on the Low and Mid groups to explore the underlying mechanisms. Metagenomics analyses showed that supplementation of freeze-dried treatment with the Mid-level supplementation significantly increased the relative abundance of propionate-producing bacteria such as Prevotella, Ruminobacter, and Succinivibrio, while inhibited acetate-producing bacteria such as Ruminococcus, altered the pattern of volatile fatty acid (VFA) synthesis in the rumen, and reduced H2 availability for methanogenesis and promoted propionate production, indirectly alleviating CH4 production. Moreover, by suppressing the relative abundance of Methanobrevibacter, CH4 production in the rumen was directly suppressed. Furthermore, KEGG pathway analysis showed that A. taxiformis significantly inhibited the abundance of K00399, methyl-coenzyme M reductase alpha subunit, which directly inhibited CH4 synthesis. Metabolomics analysis of A. taxiformis supplementation significantly enriched ketoglutarate, malate, isocitrate, and melatonin, which may have reduced the release of rumen fermented H2, thereby mitigating CH4 emissions. In summary, freeze-dried treatment A. taxiformis at the 5% supplementation level achieved the optimal balance between CH4 mitigation and rumen fermentation efficiency.